2002
DOI: 10.1053/jhep.2002.36365
|View full text |Cite
|
Sign up to set email alerts
|

Region selective alterations of soluble guanylate cyclase content and modulation in brain of cirrhotic patients

Abstract: Modulation of soluble guanylate cyclase (sGC) by nitric oxide (NO) is altered in brain from experimental animals with hyperammonemia with or without liver failure. The aim of this work was to assess the content and modulation of sGC in brain in chronic liver failure in humans. Expression of the ␣-1, ␣-2, and ␤-1 subunits of sGC was measured by immunoblotting in autopsied frontal cortex and cerebellum from cirrhotic patients and controls. The contents of ␣-1 and ␣-2 subunits of guanylate cyclase was increased b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…These results corroborate the earlier reports on speeling effects of hyperammonemia or HE on the expression in astrocytic markers [40]. The ammonia concentration in brain (1-5 mM) in the primary cortical astrocytes had lead to a destabilization mRNA expression of GFAP [41][42][43].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results corroborate the earlier reports on speeling effects of hyperammonemia or HE on the expression in astrocytic markers [40]. The ammonia concentration in brain (1-5 mM) in the primary cortical astrocytes had lead to a destabilization mRNA expression of GFAP [41][42][43].…”
Section: Discussionsupporting
confidence: 91%
“…Our administration could also increase the ammonia level in brain to the range 1-5 mM [12]. Liver failure during hyperammonemia is well-known to diminish the level of sGC via NO in (brain) as documented in liver cirrhotic patients [33,40]. The diminished levels of sGC by NO and hence the glutamate-NO-cGMP pathway could be involved in different neurological modifications found in HE.…”
Section: Discussionmentioning
confidence: 76%
“…Reduction of sGC expression in human glioma tissues and cell lines. sGC expression in glioma cell lines (U87, U251, U373, A172, LN18, LN229, and D54) was examined by Western blot (A) and real time-Q-PCR (B) and compared with that in BE2 human neuroblastoma cell line, which normally expresses both sGC ␣1 and ␤1 subunits at levels similar to those in normal human cortex (D) (Bonkale et al, 1995;Corbalá n et al, 2002;Sharina et al, 2008). The GEO database analysis of sGC gene expression in human glioma tissues of different grade (C) showed that the expression of sGC ␣1 and ␤1 is markedly decreased in astrocytoma (n ϭ 26), oligodendrocytoma (n ϭ 50), and glioblastoma multiforme (n ϭ 81) compared with normal brain tissues (n ϭ 23).…”
Section: Resultsmentioning
confidence: 99%
“…7,8 This modulation is altered in patients who have died of hepatic encephalopathy, as it is in rats with portacaval anastomosis. 10 Therefore, the function of the glutamate-NO-cGMP pathway also should be altered in the brains of these patients as in rats with portacaval anastomosis and also should be responsible for the impairment of some intellectual functions.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Chronic hyperammonemia also impairs the ability of rats to learn a conditional discrimination task. 9 The step of the glutamate-NO-cGMP pathway altered in rat models of hyperammonemia and hepatic encephalopathy is the activation of soluble guanylate cyclase by NO, 8,10 which is also altered in brains of patients who died with hepatic encephalopathy. 10 We hypothesized that the alterations in the function of the glutamate-NO-cGMP pathway in the brain in hyperammonemia and liver disease may be responsible for the impairment in learning ability and intellectual function and that pharmacological modulation of the pathway may restore learning ability in hyperammonemia and hepatic encephalopathy.…”
mentioning
confidence: 99%